Ankyloglossia and its surgical correction by frenuloplasty in a she-camel calf (Camelus dromedarius) - Anwar, S. (Open Vet J, 2012)
A rare case of ankyloglossia in a one-humped camel and its successful surgical correction by horizontal to vertical frenuloplasty is reported. Seven-month-old she-camel calf, with a history of excessive salivation and inability to chew and swallow hay, was referred to Al Qattara veterinary hospital. Solid food was regurgitated, whereas milk and water could be swallowed. On examination; the animal could not protrude its tongue which was attached by a thin tissue band between the ventral surface of the tongue and the floor of the oral cavity. The tissue band was corrected by frenuloplasty and the incisions were sutured. The animal recovered well as the salivation and regurgitation stopped and the animal became able to chew and swallow solid food including hay. It was concluded that ankyloglossia can occur in one-humped camel in which a horizontal to vertical frenuloplasty may improve full function of tongue movement.